The development of conceptual model for leader's nonverbal communication in the construction industry / Mahdieh Mohammadi, Hafez Salleh, Mahanim Hanid - Mohammadi, Mahdieh; Salleh, Hafez; Hanid, Mahanim (Research Management Institute (RMI), 2023)
Nonverbal communication comprises an essential part of the interactions between leader and follower. Although numerous studies have been conducted on nonverbal communication in multiple industries, there has been limited attention given to the effect of nonverbal communication in the construction industry. Additionally, there is a lack of a reliable model for a leader's nonverbal communication in construction. Therefore, this study specifically aims to contribute to this gap by linking leaders' nonverbal communication to an under-researched outcome of the leader-follower relationship, namely, followers' job satisfaction. This study also emphasises the mediating effect of followers' emotions in the afore mentioned relationship. For this purpose, the literature review is built upon nonverbal communication, job satisfaction, and emotion, which were identified through scientific manuscripts and electronic databases. Consequently, this study proposes a model for the leader's nonverbal communication and followers' job satisfaction. The literature review illustrates the significance of nonverbal communication in the construction industry to improve the productivity and effectiveness of followers. This research suggests investigating the proposed model virtually and developing deeper insights on leaders' nonverbal communication and its possible impact on job satisfaction.